Bronze Age copper sources in the Mediterranean : a new approach - Gale, N; Stos-Gale, Z (American Association for the Advancement of Science, 1982)
Efforts by scientists to locate the sources of copper used in ancient Mediterranean and Near Eastern cultures through comparative chemical analyses of copper ores and archaeological artifacts have largely failed for various mineralogical and metallurgical reasons. The isotopic composition of lead, an element present in a minor amount in many copper ores and bronze objects, is unchanged through metallurgical processes and may in principle be used to determine the sources of the copper used in Bronze Age artifacts. Results suggest that for Late Bronze Age Crete the Laurion region in Attica, Greece, may have been a more important copper source than Cyprus.